QS10: The Lysosomal Trafficking Regulator (LYST) Protein is a Novel and Essential Mediator of Cutaneous Wound Healing. (July 2021) - Barker, Jenny C.; Zbinden, Jacob; Mirhaidari, Gabriel; Blum, Kevin; Breuer, Christopher
Abstract : Purpose: In 2009, chronic wounds were a major public health threat affecting 2% of the population, and the estimated cost of caring for the 6.5 million people in the U.S. with chronic wounds was 50 billion dollars per year [1]. By 2019, 8.2 million people were wound care patients amongst Medicare beneficiaries, with a higher cost range for care of 28.1 - 96.8 billion dollars [2]. This prevalence and cost burden highlight the increasing nature of the chronic wound problem. Despite the biologic complexity and phylogenetic conservation, basic understanding of wound biology has been limited to relatively few specific fields of study. Little is known about how entire organelle systems, such as endolysosomal-mediated protein trafficking, regulate cutaneous wound healing. Methods: We have uncovered a novel and essential regulator of cutaneous wound healing; the Lysosomal Trafficking Regulator (LYST). LYST is a widely expressed gene encoding a protein that regulates intracellular protein trafficking from secretory lysosomes, but the mechanisms underlying its function are unknown. The Beige mouse model possesses a spontaneously occurring mutation in the LYST gene. We utilized a splinted, excisional wound model to characterize wound healing in the Beige mouse to evaluate the role of LYST in normal wound healing. Results: We observed a significant delay to healing (13.7 +/- 1.0 days, C57Bl/6 vs. 16.7 +/- 2.1 days, Beige, p = 0.0098), decreased extracellular matrix (ECM) deposition (60.8 +/- 10.5% collagen density, C57Bl/6 vs. 50.5 +/- 9.9% collagen density, Beige, p = 0.0321), and delayed epithelialization (94.6 +/- 17.1% epithelialized, C57Bl/6 vs. 58.5 +/- 30.0% epithelialized, Beige, p = 0.0044) in Beige wounds. No differences were observed for macrophage infiltration, phenotype or neovascularization. Next, we evaluated protein secretion profiles from primary dermal fibroblasts from Beige and C57Bl/6 mice. Beige fibroblasts demonstrated decreased ability to secrete monocyte chemoattractant protein-1 (MCP-1) (17294 +/- 563 relative optical density (OD), C57Bl/6 vs. 10519 +/- 2348 relative OD, Beige, p = 0.0083) and members of the insulin-like growth factor regulatory axis, IGF-1 and IGFBP2 (IGF-1; 473.8 +/- 40.6 relative OD, C57Bl/6 vs. 149.8 +/- 133.7 relative OD, Beige, p = 0.0159 and IGFBP2; 17918 +/- 664 relative OD, C57Bl/6 vs. 15451 +/- 690 relative OD, Beige, p = 0.0111). While these are known mediators for normal wound healing, specifically, for wound epithelialization and ECM deposition [3-5], the role of LYST in their intracellular protein trafficking and exocytosis has not been previously described. Interestingly, IGF-1 does rely on well-established exocytic pathways reliant on the synaptotagmin family of proteins [6]. These findings, therefore, provide new insight into the intracellular mechanism of action of the LYST protein, which has previously remained elusive. Conclusions: LYST is important for the secretion of chemokines and growth factors that play an important role in regulating normal wound healing. The expansion of knowledge towards a fundamental understanding of diverse cellular processes involved in normal wound healing, such as endolysosomal trafficking, is important because it provides new lines of investigation for therapeutic strategies to address problem wounds.